TIGA JENIS ALAT TANGKAP KEKUAK UNTUK TUJUAN KOMERSIAL DI BANGKA Studi Kasus Pebuar (Bangka Barat) dan P.Nangkabesar (Bangka Tengah) - YULIAN FAKHRURROZI; JOHN HALUAN; ARI PURBAYANTO; SOEWARNO T. SOEKARTO (Akuatik: Jurnal Sumberdaya Perairan, 2009)
This paper describes the research result about catching gears in traditional-commercial kekuak catch fishery in Bangka at two production centres, Pebuar and Nangkabesar. The objectives is exploring and comparing the gears which used for catching kekuak. Data were collected by observation at fishing activities and interview with key informans. The research found there are three kinds of gear: cucok, rangkang dan serampang. Cucok is the gear came from ancient tradition, but rangkang, and serampang came from fishermen innovation. The cucok is used at all of regions in Bangka, but the rangkang is used only at Pebuar, and the serampang only at Nangkabesar